Anticitrullinated protein antibodies facilitate migration of synovial tissue-derived fibroblasts. Issue 12 (3rd September 2019) - Sun, Meng; Rethi, Bence; Krishnamurthy, Akilan; Joshua, Vijay; Circiumaru, Alexandra; Hensvold, Aase Haj; Ossipova, Elena; Grönwall, Caroline; Liu, Yanying; Engstrom, Marianne; Catrina, Sergiu Bogdan; Steen, Johanna; et al.
Abstract : Objectives: Rheumatoid arthritis (RA)-specific anti-citrullinated protein/peptide antibodies (ACPAs) might contribute to bone loss and arthralgia before the onset of joint inflammation. We aimed to dissect additional mechanisms by which ACPAs might contribute to development of joint pathology. Methods: Fibroblast-like synoviocytes (FLS) were isolated from the synovial membrane of patients with RA. The FLS cultures were stimulated with polyclonal ACPAs (anti-CCP-2 antibodies) purified from the peripheral blood of patients with RA or with monoclonal ACPAs derived from single synovial fluid B cells. We analysed how ACPAs modulate FLS by measuring cell adhesion and mobility as well as cytokine production. Expression of protein arginine deiminase (PAD) enzymes and protein citrullination were analysed by immunofluorescence, and signal transduction was studied using immunoblotting. Results: Challenge of FLS by starvation-induced stress or by exposure to the chemokine interleukin-8 was essential to sensitise the cells to ACPAs. These challenges led to an increased PAD expression and protein citrullination and an ACPA-mediated induction of FLS migration through a mechanism involving phosphoinositide 3-kinase activation. Inhibition of the PAD enzymes or competition with soluble citrullinated proteins or peptides completely abolished the ACPA-induced FLS migration. Different monoclonal ACPAs triggered distinct cellular effects in either fibroblasts or osteoclasts, suggesting unique roles for individual ACPA clones in disease pathogenesis. Conclusion: We propose that transient synovial insults in the presence of a certain pre-existing ACPA repertoire might result in an ACPA-mediated increase of FLS migration.